A percepção de atitudes em relação ao sotaque de comunidade caiçara do Litoral Norte de São Paulo - Oliveira, Marta Aparecida de Faria Tanuri (2020)
Populations born and living in coastal regions, specifically in the southeastern coast of Brazil, are called caiçaras. They present linguistic and cultural typicality that manifests itself, among other domains, in speech, dance, handicraft, music and cooking. This paper aims to investigate the impressions of a group of listeners, the research judges, based on the characteristics of the caiçara speech accent by means of the application of a semantic differential questionnaire, which contains descriptors referring to psychological, social and cultural physical and economic attributes. It is, therefore, a sociophonetic perceptive study that comprises a production task and a perception task. The research corpus is composed of semi-spontaneous speech recordings of subjects from the caiçara community. The subjects of the speech production task are 11 men and 11 women between 41 and 91 years old, residents of the North Coast of São Paulo State. The subjects of the perception task, referred to as judges, are 90 adults of both sexes, originary from the states of São Paulo (North Coast and capital) and Rio de Janeiro. A sociolinguistic profile of the subjects of the production task was performed. For the application to the judges of the perception task, which comprised the semantic differential questionnaire, a script was used and as a statistical method of investigation the multidimensional analysis was applied. From the results obtained from the analysis of 1980 responses to the semantic differential questionnaire applied, we have identified attitudes towards the speech variety of the caiçara community of the North Coast of São Paulo. The speech of the caiçara community was considered unpleasant by the judges of all places and caused no strangeness or misunderstanding. Therefore, the caiçara speech was judged as unpleasant, very understandable and very common. The results of the application of the multidimensional analysis test, considering the significant variables with a correlation percentage above 80%, showed that the caiçaras speakers were judged based on the perception of their speech, as people who perform manual work, have a bad financial situation, are unsuccessful, naive, simple and humble